2009
DOI: 10.1002/crq.234
|View full text |Cite
|
Sign up to set email alerts
|

Mediation by any other name would smell as sweet—or would it? The struggle to define mediation and its various approaches

Abstract: This article reports on two studies. The analysis of the first study, a survey of 250 mediators, finds four distinct groups of mediator “clusters,” based on self‐reported strategies. These four clusters are described in detail and mediators' self‐defined labels are then correlated with the four clusters. There is little consistency between the labels mediators give their approach and the cluster into which they actually fall in this survey. The analysis of the second study, which involved observation and codin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 5 publications
3
62
0
Order By: Relevance
“…Supporting this contention, Della Noce (2009) recently reported that in a study of the types of mediation practiced by practitioners, 62% of the sample claimed to practice evaluative mediation, either alone or in combination with other mediation approaches (i.e., facilitative or transformative). Likewise, Intermittent Evaluative Mediation 149 Charkoudian, De Ritis, Buck, and Wilson (2009), in their study of mediator approaches and techniques, found that mediators who reported using evaluative strategies do not give themselves the label of directive or evaluative.…”
Section: What Child Custody Evaluators Can Bring To the Mediation Tablementioning
confidence: 93%
“…Supporting this contention, Della Noce (2009) recently reported that in a study of the types of mediation practiced by practitioners, 62% of the sample claimed to practice evaluative mediation, either alone or in combination with other mediation approaches (i.e., facilitative or transformative). Likewise, Intermittent Evaluative Mediation 149 Charkoudian, De Ritis, Buck, and Wilson (2009), in their study of mediator approaches and techniques, found that mediators who reported using evaluative strategies do not give themselves the label of directive or evaluative.…”
Section: What Child Custody Evaluators Can Bring To the Mediation Tablementioning
confidence: 93%
“…As prior research has shown, neutrals who identify with a particular framework engage in behaviors inconsistent with that orientation (Charkoudian et al, 2009;Golann, 2000;Wissler, 2004). In both processes, a third-party neutral assists the parties in discussing the dispute and negotiating potential options for resolution, using a range of strategies in the process.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, neutrals vary in their training and approach and the specific techniques used throughout the ADR session (Charkoudian, de Ritis, Buck, & Wilson, 2009;Riskin, 2003). Yet, neutrals vary in their training and approach and the specific techniques used throughout the ADR session (Charkoudian, de Ritis, Buck, & Wilson, 2009;Riskin, 2003).…”
mentioning
confidence: 99%
“…Third, as indicated earlier, we assessed the mediators preferred style using Kressel's (2007) categorization: facilitative, evaluative, strategic, transformational, narrative and victim-orientated. Fourth, we also wanted to control for the goals of the mediation as perceived by the mediator using the five-item scale developed by Charkoudian et al (2009), which asks to what extent the following were goals of the mediation: agreement, clarity about needs and choices, understanding of each other, control of the outcome and ability to resolve future conflicts.…”
Section: Methodsmentioning
confidence: 99%